DEGRADATION WORKS OF MONUMENTAL ART CAST BRONZE UNDER THE INFLUENCE OF ENVIRONMENTAL FACTORS - Delia NICA-BADEA; Minodora Maria PASĂRE (Fiabilitate şi Durabilitate)
Intensive pollution, combined with the lack of conservation of monuments exposed to these environments make the main cause of deterioration of cultural objects to atmospheric corrosion metal. This paper proposes a study of the main factors leading to degradation Bronze alloy, cast bronze monuments exposed to open atmosphere: corrosive environmental factors, stability and products of corrosion of bronze. In general, all corrosion products present on a metal surface are indicated as 'skate', can be composed of single-layer or multilayer products. The paper also includes a case study on the influence of environmental factors on degradation Matthias monument statue in Cluj-Napoca, Romania. Visual inspection of the monument informs us that have white spots, gray, reddish not consistent with the base color green patina, surfaces showing depigmentation, the rain washed areas, crystallization, deposition of air-borne particles.